Evidencia fotográfica de especies desconocidas de onicóforos (Onychophora: Peripatidae) de Costa Rica - Barquero González, José Pablo (2016)
Onychophorans are hard to find and identify to species under field conditions. Currently, there are seven species described from Costa Rica, and an appropriate taxonomic revision is necessary. However, technology allows the documentation of rare and even undescribed species. Here we compile donated photographs and online images to identify 18 new Costa Rican species (based on taxonomic characteristics or geographical distribution). In addition we present relevant scientific information for each. Although it is not possible to make a formal description of species from photographs, this compilation shows where they can be searched for future research. Our goal is to preserve this information and to raise awareness among biology students and nature photographers about the importance of finding an onychophoran. These findings frequently result in new species discoveries.